Inovasi Kurikulum Pengembangan Metode Demontrasi Dalam Praktik Qurban di SMK - Komariah, Cucu; Nurhakim , Aam; Al Fajar, Fahrurroji Firman; Badruddin, Badruddin; Yulianti, Qiqi Zakiah (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This research aims to develop curriculum innovation through demonstration methods in the practice of qurban in vocational schools. The background of this research is the lack of ability and skills of vocational school students in cutting qurbani. The methodology used is narrative qualitative with literature study. This research emphasizes the importance of reading and writing literacy, which includes the ability to read, write, search, browse, process and understand information in order to analyze and respond to written texts, as well as to achieve goals, develop students' understanding and potential. The aim of this research is to determine the effectiveness of the demonstration method in the practice of qurban in vocational schools. The results of the research show that vocational school students can recite prayers when slaughtering sacrificial animals, understand and carry out the terms of sacrifice, as well as practical skills such as slicing animal skin, cleaning the stomach, cutting ivory, grouping and weighing sacrificial meat, and distributing it to those entitled to it. Apart from that, this method also increases students' faith and piety, and instills values from the story of Prophet Ismail As. and Prophet Ibrahim As. The demonstration method has proven effective in increasing students' understanding and skills regarding sacrifice, as well as in fostering positive social and religious attitudes.